Effects of Early Cumulus Cell Removal on Treatment Outcomes in Patients Undergoing In Vitro Fertilization: A Retrospective Cohort Study - Kong, Pengcheng; Yin, Mingru; Tang, Chuanling; Zhu, Xiuxian; Bukulmez, Orhan; Chen, Miaoxin; Teng, Xiaoming (Frontiers in Endocrinology, 2021)
Background: Early cumulus cell removal combined with early rescue intracytoplasmic sperm injection (ICSI) has been widely practiced in many in vitro fertilization (IVF) centers in China in order to avoid total fertilization failure. However, uncertainty remains whether the pregnancy and neonatal outcomes are associated with early cumulus cell removal. Objectives: To investigate if early cumulus cell removal alone after 4 hours co-incubation of gametes (4 h group), has detrimental effect on the pregnancy and neonatal outcomes in patients undergoing IVF, through a comparison with conventional cumulus cell removal after 20 hours of insemination (20 h group). Methods: This retrospective cohort study included 1784 patients who underwent their first fresh cleavage embryo transfer at the Centre for Assisted Reproduction of Shanghai First Maternity and Infant Hospital from June 2016 to December 2018 (4 h group, n=570; 20 h group, n=1214). A logistic regression analysis was performed to examine the independent association between early cumulus cell removal and pregnancy outcomes after adjustment for potential confounders. The neonatal outcomes between the two groups were compared. Results: When compared with the 20 h group, the 4 h group had similar pregnancy outcomes, including rates for biochemical pregnancy, clinical pregnancy, ongoing pregnancy, miscarriage, ectopic pregnancy, multiple pregnancy, and live birth. There were 1073 infants delivered after embryo transfer (4 h group, n=337; 20 h group, n=736). Outcomes in both groups were similar for both singleton and twin gestations, including preterm birth rates and very preterm birth rates, mean birth weight, mean gestational age, sex ratio at birth and rate of congenital birth defects. In addition, findings pertaining to singleton gestations were also similar in the two groups for Z-scores (gestational age- and sex-adjusted birthweight), rates of small for gestational age, very small for gestational age, large for gestational age and very large for gestational age infants. Conclusions: In this study early cumulus cell removal alone was not associated with adverse pregnancy and neonatal outcomes. From this perspective, early cumulus cell removal to assess for a potential early rescue ICSI is therefore considered to be safe option in patients undergoing IVF.